Studi Literatur Review: Efek Pemberian Genistein untuk Mengatasi Beberapa Penyakit Kardiovaskular - Dinda Dewi Maysayu Wibisana (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2025)
Cardiovascular is a heart or blood vessel disorder that is the leading cause of death in the world. Genistein is one of the phytochemicals contained in soybeans that has estrogenic properties and can help in dealing with cardiovascular diseases, such as hypertension, lipid profile disorder (dislipidemia), hypertrophy and so on. According to the FDA, the limit of soy consumption to get the beneficial effects of genistein is 25 grams. Excessive consumption can cause side effects such as hypothyroidism, testosterone imbalance, allergic hypersensitivity in children, and cancer cell proliferation. This review literature study explores the mechanisms of genistein against several cardiovascular diseases. In the search for English articles, the keywords used to get articles that match the criteria are “genistein”, “cardiovascular”, “hypertrophy”, “Hypertension”, “blood pressure”, and “lipid profile” and have been published for 10 years. The database used in the article search is PubMed and Science Direct. Based on the exclusion and inclusion of the article selection, there are 6 articles worthy of further examination. A sixth study in the journal found that genistein can improve lipid profiles, lower blood pressure, and decrease pulmonary hypertrophy. Genistein has estrogenic, anti-inflammatory, antioxidant, and immunomodulatory properties that can help reduce cardiovascular disease. There are several factors that influence the effectiveness of genistein, namely diet, physical activity, interaction with other nutrients, duration of consumption, and dosage of genystein intake.